Sleep characteristics and menstrual cycle phase-based differences in sleep in naturally menstruating elite female team sport athletes - McGeever, A.; Mallon, N.; Bruinvels, G.; Pedlar, C. R.; Doherty, R.; Van Someren, K. A. (European Journal of Sport Science, 2026)
ABSTRACT This study examined the sleep characteristics and menstrual cycle (MC) phase-based differences in the sleep of naturally menstruating female team sport athletes. Twelve Senior Intercounty Ladies Gaelic Football players (age = 24.2 ± 4.0 years) were recruited for the study. This study involved the prospective monitoring of participants for approximately 3 months, aiming to capture data for three full MCs. Participants were required to wear an Oura ring to objectively monitor sleep and physiological variables whilst also completing daily sleep diaries. Participants tracked their MC and cycle-related symptom prevalence using a smartphone application and estimated ovulation via urinary testing kits. A perception-reality gap was identified, with participants' objective sleep being 55 min less than their subjective sleep. Objective sleep quality measures fluctuated across the MC. Sleep efficiency decreased and wake after sleep onset and sleep onset latency increased in Phase 1 (menstruation), whereas wake events were significantly higher in Phase 4 (pre-menstrual). There were no significant differences in subjective sleep metrics across MC phases. The prevalence and perceived impact of cycle-related symptoms peaked in Phase 1 and Phase 4, aligning directly with the timing of objective sleep disruptions. Therefore, monitoring sleep and MC characteristics may be useful for female athletes to identify timepoints where sleep may be disrupted and help them to identify possible mitigation strategies should sleep disturbances occur.